Case report of an influenza outbreak in the sports medicine setting - Fisher, K.; Frank, E.; Andrie, J.; Onks, C. (Current Sports Medicine Reports, 2021)
The seasonal influenza virus affects people of all ages and demographics. In the United States, it is responsible for more than 200,000 hospitalizations and 30,000 to 50,000 deaths annually (1). Robust recommendations guide health care professionals in prevention, chemoprophylaxis, and treatment of influenza (2). However, no clear chemoprophylaxis guidelines exist for athletic teams, who are at increased risk of transmitting infectious disease. The American Academy of Pediatrics and the Infectious Disease Society of America (IDSA) published well-researched chemoprophylaxis recommendations for adults, children, and individuals potentially in close contact with someone who has influenza, but no clear mention of how athletic team members fit into the guidelines (3,4). There is little published on the role of the athletic training staff and sports medicine team in influenza prevention and outbreaks management. This case report highlights the integral role of the sports medicine team in instituting preventive measures, addressing an outbreak, and recommending a comprehensive treatment approach that includes influenza vaccination. This case took place in the winter months before the COVID-19 pandemic. Lessons learned during the pandemic will help to formulate infectious disease management programs that in the future will need to address not only influenza, but other viruses including COVID-19 in the sports medicine setting.